Studi Kasus Keabsahan Penggunaan Bahasa Asing Dalam Loan Agreement Nine Am Ltd di Indonesia - Ricco Adhi Laksana; Eko Rial Nugroho (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study aims to analyze the decision of the Supreme Court (MA) rejecting the cassation submitted by Nine AM Ltd. Based on two previous decisions, namely the DKI Jakarta High Court Decision Number 48/PDT/2014/PT.DKI dated 7 May 2014 and the West Jakarta District Court Decision Number 451/PDT.G/2013/PN JKT.BRT dated 20 June 2013, the Supreme Court considered that agreements that were only available in English were legally invalid because they violated Article 31 of the Language Law and violated the clauses as regulated in Article 1335 jo. Article 1337 of the Civil Code, then then is the use of a foreign language, namely English, legally invalid? Based on this problem, the conclusion is that:1. Article 31 of the Language Law regulates the obligation to use Indonesian, but there is no threat of sanctions. 2. Article 31 paragraph (2) of the Language Law also provides parties with the opportunity to write contracts in English. 3. Notarial Law Article 43 paragraph (3) which provides the opportunity for deeds to be made in a foreign language. 4. The lawful cause or cause of an agreement is the content of the agreement itself, not the language used.